Ventricular tachycardia ablation in nonischemic cardiomyopathy. (14th October 2021) - Nascimento Matos, D; Cavaco, D; Cavaco, D; Carmo, P; Carmo, P; Carvalho, M.S; Carvalho, M.S; Rodrigues, G; Rodrigues, G; Carmo, J; Carmo, J; Galvao Santos, P; et al.
Abstract: Introduction: Catheter ablation outcomes for drug-resistant ventricular tachycardia (VT) in nonischemic cardiomyopathy (NICM) are suboptimal when compared to ischemic cardiomyopathy. We aimed to analyse the long-term efficacy and safety of percutaneous catheter ablation in this subset of patients. Methods: Single-center observational retrospective registry including consecutive NICM patients who underwent catheter ablation for drug-resistant VT during a 10-year period. The efficacy endpoint was defined as VT-free survival after catheter ablation, while safety outcomes were defined by 30-days mortality and procedure-related complications. Independent predictors of VT recurrence were assessed by Cox regression. Results: In a population of 68 patients, most were male (85%), mean left ventricular ejection fraction (LVEF) was 34±12%, and mean age was 58±15 years. All patients had an implantable cardioverter-defibrillator. Twenty-six (38%) patients underwent epicardial ablation (table 1). Over a median follow-up of 3 years (IQR 1–8), 41% (n=31) patients had VT recurrence and 28% died (n=19). Multivariate survival analysis identified LVEF (HR= 0.98; 95% CI 0.92–0.99, p=0.046) and VT storm at presentation (HR=2.38; 95% CI 1.04–5.46, p=0.041) as independent predictors of VT recurrence. The yearly rates of VT recurrence and overall mortality were 21%/year and 10%/year, respectively. No patients died at 30-days post-procedure, and mean hospital length of stay was 5±6 days. The complication rate was 7% (n=5, table 1), mostly in patients undergoing epicardial ablation (4 vs 1 in endocardial ablation, P=0.046). Conclusion: LVEF and VT storm at presentation were independent predictors of VT recurrence in NICM patients after catheter ablation. While clinical outcomes can be improved with further technical and scientific development, a tailored endocardial/epicardial approach was safe, with low overall number of complications and no 30-days mortality. Funding Acknowledgement: Type of funding sources: None.